The Relationship Between the FRAX Tool and Bone Turnover Markers in Postmenopausal Osteoporosis - Murat Uludağ; Ülkü Akarırmak; Murat Bolayırlı (Galenos Yayinevi, 2013)
Aim: In this study, we aimed to show the correlation between the ten-year fracture risk, calculated with FRAX and bone turnover markers (BTM) in a group of postmenopausal women with osteoporosis. Material and Methods: Twenty-four postmenopausal women diagnosed as osteoporosis were included. Patients were assessed for duration of menopause, secondary diseases, medication, habits of nutrition, previous fracture, and family history of fracture. Weight and height measurements were obtained. Bone mineral density (BMD) was measured by dual-energy X-ray absorptiometry (DXA), with a Hologic-QDR 4500 plus device. The ten-year risk for major as well as hip fractures were calculated with the FRAX tool. Serum calcium, phosphorus, magnesium, 25-OH Vitamin D, parathormone (PTH), alkaline phosphatase (ALP), and biochemical markers of bone formation (Osteocalcin, Bone-ALP) and resorption ( N-terminal collagen type 1 and C terminal collagen type 1) were determined. Results: The mean age of patients was 64.3±8.6 (46-80 years). The mean ten-year major fracture and hip fracture risks were 19.5±6.2% and 16.0±5.1%, respectively. There was a strong correlation between the duration of menopause and hip fracture risk (r: 0.878, p=0.022). There was also a strong relationship between hip fracture risk and NTX (r: 0.759, p=0.042). Conclusion: Resorption markers of bone turnover are relevant components in determining fracture risk. Rate of bone remodeling is a parameter which is not included in the FRAX tool. Since FRAX is an established tool for assessing the ten-year fracture risk, we assessed and found a correlation between hip fracture risk and NTX. Further studies, in larger groups of patients need to make clear the impact of BTM in this tool. (Turkish Journal of Osteoporosis 2013;19: 38-41)